Moringa oleifera Leaf Ethanol Extract Inhibits Toxoplasma gondii Tachyzoites Replication - Wihanto, Laura; Waworuntu, Gladdy Lysias; Tedyanto, Cecilia Putri; Puspitasari, Heni (Indonesian Journal of Tropical and Infectious Disease, 2023)
The various infection routes of Toxoplasma gondii that are close to daily life strongly support the incidence of toxoplasmosis. The emergence of drug-resistant Toxoplasma gondii strains raises future concerns. Moringa leaf ethanol extract has been shown to have several anti-pathogen activities, which could have an anti-Toxoplasma effect. This research was conducted to analyze the anti-Toxoplasma effect of moringa leaf ethanol extract against tachyzoites replication in Toxoplasma gondii and the correlation between extract doses with the number of tachyzoites. Mice were divided into five groups. The negative control group (Group I) received CMC-Na solution. The positive control group (Group II) received spiramycin 100 mg/kg BW. The treatment groups received moringa leaf ethanol extract 250 mg/kg BW (group III), 500 mg/kg BW (group IV), and 1000 mg/kg BW (group V), respectively. Mice were injected with 1 x 105 tachyzoites/0.1 mL/mice intraperitoneally on the first day. Moringa leaf ethanol extract and spiramycin were given orally once daily for three days. The number of tachyzoites in the intraperitoneal fluid was calculated on the fifth day. The results have shown that there were significantly lower differences (P < 0.05) in group IV (P = 0.021) and group V (P = 0.022) compared to group I. There was also a significant negative correlation between the extract doses and the number of tachyzoites (P = 0.000; r = -0.781). Moringa oleifera leaf ethanol extract has an anti-Toxoplasma effect by inhibiting the tachyzoite replication at     500 mg/kg BW and 1000 mg/kg BW.